2017
DOI: 10.4172/pharmaceutical-sciences.1000319
|View full text |Cite
|
Sign up to set email alerts
|

Drug Utilization Study of Psychotropic Drugs among Psychiatric Outpatients in a Tertiary Care Hospital

Abstract: Chawla, et al.: Drug Utilization Study of Psychotropic DrugsAvailability and utilization of a wide variety of psychotropic drugs is associated with a wide spectrum of adverse drug reactions. To ensure the rational use of psychotropic drugs, it is imperative to monitor their pattern of use. The present study mainly focuses on the pattern of utilization of psychotropic drugs among psychiatric outpatients in a tertiary care hospital. A hospital based cross sectional study was carried out in the psychiatry outpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…Higher number of drugs per encounter can increase the risk of drug interactions, dispensing errors, patient not knowing correct dosage schedule, patient noncompliance and increased cost. 11 Out of the total 291 drugs prescribed only 2.06% of the drugs were prescribed by generic name which is much less when compared to the WHO standards. 8 WHO highly recommends prescribing medications by generic name as a safety precaution for patients because it identifies the drug clearly, enables better information exchange and allows better communication between health care providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher number of drugs per encounter can increase the risk of drug interactions, dispensing errors, patient not knowing correct dosage schedule, patient noncompliance and increased cost. 11 Out of the total 291 drugs prescribed only 2.06% of the drugs were prescribed by generic name which is much less when compared to the WHO standards. 8 WHO highly recommends prescribing medications by generic name as a safety precaution for patients because it identifies the drug clearly, enables better information exchange and allows better communication between health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…most of our patients. 11 Giving drugs in the form of injections is not a common practice in psychiatry, barring emergency situations. The percentage of encounters with an injectable prescribed in this study was only 0.03% when compared to study done by Nandagopal et al 8 In this study out of the total 237 psychotropic drugs, 41.77% of psychotropic drugs were prescribed from NLEM (2015) and 17.72% from the WHO model list of essential medicines (2017).…”
Section: Fdc Non Fdcmentioning
confidence: 99%
“…This finding is consistent with the finding in the 2012 study by Chawla et al, which reported that the most widely used drug among patients with bipolar disorder in India was sodium valproate (54.7%). 43 In addition, a 2009 study involving bipolar disorder outpatients in South Africa mentioned that most patients (83.8%) were prescribed at least one standard mood stabilizer and that sodium valproate was the most prescribed mood stabilizer (37.1%). 44 The National Institute for Health and Care Excellence (NICE) has recommended the use of valproate as first-line therapy in acute manic episodes.…”
Section: Discussionmentioning
confidence: 99%
“…above 18 years) globally is estimated at 10 %. 10 The public health burden is greatest among low and middle-income countries such as Namibia. In Namibia, the prevalence of mental illnesses is estimated at 25.6% 11 and is expected to double by 2025.…”
Section: Introductionmentioning
confidence: 99%